(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
In spite of the fact that there is a growing trend toward deinstitutionalization on a worldwide scale, mental asylums continue to be an essential component of psychiatric care in a variety of settings. The purpose of this study is to investigate the social elements of living in mental asylums, with a particular focus on stigma, isolation, and perceptions of rehabilitation among patients, caregivers, staff, and the general population. An observational study that was quantitative and cross-sectional was carried out with a total of two hundred participants. The effects of stigma, isolation, and recovery were evaluated using standardized scales, and the data were analyzed using analysis of variance (ANOVA) with post-hoc comparisons. Despite the fact that patients and the general population had significantly higher scores for stigma and isolation, the results showed that workers had the most positive views toward rehabilitation. These findings highlight the disparity between the experiences that patients have really lived through and the perceptions that healthcare practitioners have, highlighting the vital demand for mental changes that are focused on rehabilitation and with the goal of decreasing stigma.